1998
DOI: 10.1002/(sici)1097-4636(19981215)42:4<491::aid-jbm3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic bone formation via rhBMP-2 delivery from porous bioabsorbable polymer scaffolds

Abstract: Drug delivery devices have received considerable interest in the field of tissue engineering due to the advent of proteins that can induce proliferation and differentiation of various cells to form specific tissues and organs, for example, bone morphogenetic protein (BMP-2) for osteogenesis. In this work the delivery of a clinically relevant bioactive factor, recombinant human rhBMP-2, was tested in vivo in a rat ectopic bone induction assay. Contact radiography and radiomorphometry showed significantly more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(78 citation statements)
references
References 29 publications
2
73
1
2
Order By: Relevance
“…Several researchers have utilized this well-characterized copolymer for encapsulation and release of a wide variety of bioactive molecules and drugs including TGF-b, BMPs, IGFs, VEGF, NGF, DNA, vancomycin, gentamysin, cisplatin, and others. [261][262][263][264][265][266][267][268] To successfully fabricate and encapsulate PLGA scaffold with these molecules, a wide variety of creative approaches have been taken such as emulsion freeze-drying, 269 nano and microparticle encapsulation, [270][271][272] double emulsion solvent extraction, 273 electrospinning, [274][275][276] compression molding, 277 and others. As mentioned earlier, a fundamental problem with utilizing growth factors is their characteristic short half life in physiological environments.…”
Section: Common Copolymers In Bone Engineeringmentioning
confidence: 99%
“…Several researchers have utilized this well-characterized copolymer for encapsulation and release of a wide variety of bioactive molecules and drugs including TGF-b, BMPs, IGFs, VEGF, NGF, DNA, vancomycin, gentamysin, cisplatin, and others. [261][262][263][264][265][266][267][268] To successfully fabricate and encapsulate PLGA scaffold with these molecules, a wide variety of creative approaches have been taken such as emulsion freeze-drying, 269 nano and microparticle encapsulation, [270][271][272] double emulsion solvent extraction, 273 electrospinning, [274][275][276] compression molding, 277 and others. As mentioned earlier, a fundamental problem with utilizing growth factors is their characteristic short half life in physiological environments.…”
Section: Common Copolymers In Bone Engineeringmentioning
confidence: 99%
“…The most widely used poly(α-hydroxy ester) polymers for particle-based strategies are polylactide (PLA), polyglycolide (PGA) and their co-polymers (poly-DL-lactide-coglycolide) (PLGA) (Brekke, 1996;Hollinger and Leong, 1996;Whang et al, 1998). Their widespread use stems from the ability of these materials to serve a multitude of purposes and applications.…”
Section: Incorporation and Releasementioning
confidence: 99%
“…[25][26][27] In addition to the direct application of recombinant BMP proteins, numerous reports have confirmed the ability of adenoviral or retroviral vector-mediated gene transfer of several BMPs to induce bone formation in animal models. 18,20,21,23,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Although a plethora of studies have demonstrated the ability of several BMPs, mostly BMP-2 and BMP-7, to promote osteogenesis, it is unclear whether or not BMPs other than those currently being tested in clinical trials are more potent stimulators of new bone formation. Thus, it is important to conduct a comprehensive comparative analysis of the in vivo osteogenic activity of all BMPs.…”
Section: Introductionmentioning
confidence: 99%